(untitled) (Revista Contexto & Saúde, 2026)
This study aimed to analyze the relationship between sleep quality and perceived stress among university students during the COVID-19 pandemic. This was a cross-sectional and analytical study conducted with 163 university students. Data were collected using a Google Forms questionnaire containing socioeconomic questions, items related to academic dynamics, sleep patterns, and COVID-19 infection. The Perceived Stress Scale, 14-item version (PSS-14), was also included. Data were analyzed using the R software through descriptive and inferential statistics. Regarding sleep patterns, 112 participants (68.7%) reported changes in their sleep pattern, and 33 (20.2%) reported sleeping less than six hours per day. Self-reported sleep quality was classified as “very good” (n = 14; 8.6%), “good” (n = 84; 51.5%), “poor” (n = 55; 33.7%), and “very poor” (n = 10; 6.2%). When assessing perceived stress levels among participants, most reported that they were never able to cope with the things they had to do (57.7%), and that they sometimes dealt successfully with difficult problems in life (40.5%). When analyzing the association between variables related to sleep and perceived stress among university students during the COVID-19 pandemic, higher stress levels were associated with the absence of good sleep (p = 0.002) and poorer sleep quality (p = 0.001), as well as with sleep alterations (p = 0.001) and the degree of sleep change (p = 0.038). Furthermore, students experiencing stress sometimes or always reported changes in their sleep pattern (p < 0.05). The perceived stress experienced by participants during the COVID-19 pandemic affected sleep quality and contributed to changes in sleep patterns.